Pseudotumor Cerebri Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators from the University of Texas Southwestern Medical Center, Dallas, and centers in Philadelphia and Salt Lake City, propose updated criteria for the diagnosis of pseudotumor cerebri (PTCS) and its variations.